2023
DOI: 10.1139/er-2021-0109
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on catchment nutrient dynamics: insights from around the world

Abstract: This study is a meta-analysis of global articles on hydrological nutrient dynamics to determine trends and consensus on (1) the effects of climate change-induced hydrological and temperature drivers on nutrient dynamics and how these effects vary along the catchment continuum from land to river to lake; (2) the convergence of climate change impacts with other anthropogenic pressures (agriculture, urbanization) in nutrient dynamics; and (3) regional variability in the effects of climate change on nutrient dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 130 publications
0
3
0
Order By: Relevance
“…In recent years, it has been recognized that basic tests to evaluate the robustness of model mathematical formulations and numerical solutions are essential for proper model scrutiny, falsification, and acceptance (Clark et al, 2021a). In this study, we extended these principles to water quality simulations where the spatiotemporal complexity and interplay of process generally often give rise to highly non-linear response patterns that are difficult to disentangle in real-world applications for proper model examination (Costa et al, 2022(Costa et al, , 2020a. We prepared a total of ten tests, of which two are non-reactive (biogeochemistry deactivated), and eight are reactive (biogeochemistry activated) -see 2 of that paper.…”
Section: Test Casesmentioning
confidence: 99%
“…In recent years, it has been recognized that basic tests to evaluate the robustness of model mathematical formulations and numerical solutions are essential for proper model scrutiny, falsification, and acceptance (Clark et al, 2021a). In this study, we extended these principles to water quality simulations where the spatiotemporal complexity and interplay of process generally often give rise to highly non-linear response patterns that are difficult to disentangle in real-world applications for proper model examination (Costa et al, 2022(Costa et al, , 2020a. We prepared a total of ten tests, of which two are non-reactive (biogeochemistry deactivated), and eight are reactive (biogeochemistry activated) -see 2 of that paper.…”
Section: Test Casesmentioning
confidence: 99%
“…Especially in terrestrial ecosystems, it is still unclear whether and how humans influence the relative balance of soil C, N, P and K by inducing changes in land use. Some studies have reported a close relationship between human disturbances and elements and stoichiometric shifts in organisms, e.g., under climate change (Costa et al, 2022), N deposition (Xu, Qu, et al, 2022), changes in atmospheric CO 2 (Lockhart et al, 2023) and species invasion (Rastogi et al, 2023). Studies have reported that the reclamation of natural soils may lead to a decrease in soil nutrients (e.g., Ouyang et al, 2013; Poeplau & Don, 2013), but some conflicting results have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Ranger patrol is time and labor-intensive, limited by natural conditions like topography and climate, and struggles to achieve rapid and accurate fire source discovery [14]. Moreover, patrolling forests in adverse weather or harsh terrain conditions poses high safety risks [15]. Although satellite remote sensing can cover wide areas and provide real-time feedback, its limited resolution hampers accurate fire source positioning during the early stages of a fire [16].…”
Section: Introductionmentioning
confidence: 99%